A new species of Macrocopturus Heller (Coleoptera: Curculionidae: Conoderinae) from Guerrero, Mexico, and the description of immature stages. - Muñiz-Vélez, Raúl; Ordóñez-Reséndiz, María Magdalena (Instituto de Ecología, A.C., 2010)
A new species of Macrocopturus Heller found in Bursera citronella Mc Vaugh & Rzedowski in Guerrero, Mexico is described. M. bruserophagus, new species, is proportionally broader and more flattened above than other species of the genus, and has carinate femora armed with ventral teeth. Larvae and pupa are described also